ANALISIS KEMAMPUAN BERPIKIR KRITIS SISWA DALAM MENYELESAIKANOPEN-ENDED QUESTION PADA MATERI FLUIDA STATIS DI SMA - Maydini Eka Rizki; Albertus Djoko Lesmono; Bambang Supriadi (FKIP Universitas Jember, 2019)
AbstractScience learning is expected to be able to deliver students to meet the capabilities in the 21st century. One of the things that must be considered to change individuals who can satisfy global demands is to produce generations who have critical thinking skills that are a logical attitude in examining every belief and assumptions based on the evidence and conclusions caused. Physics lessons are considered difficult because students do not have deep thinking skills in solving physics problems. The open-ended approach provides opportunities for students to gain experience in exploring and solving problems with several techniques. The purpose of this study was to analyze students' critical thinking skills in an open-ended question solution on static fluid material in senior high school. This research is a descriptive research. The research method uses a test. The test instrument uses a descriptive question with an open-ended approach of 5 items and a questionnaire for student self-assessment. The study was conducted in class XI of SMAN 1 Cluring Banyuwangi. The results showed that the level of students' critical thinking skills in the complete of the open-ended question at SMAN 1 Cluring was quite good.Key Word: Critical Thinking Skills, Open-Ended Question, Physics